THE IMPLEMENTATION OF TOLERANCE CHARACTER EDUCATION THROUGH SOCIAL SCIENCE LEARNING IN ELEMENTARY SCHOOL - Framz Hardiansyah (Auladuna: Jurnal Pendidikan Dasar Islam, 2022)
Abstract This study aimed to determine the implementation of tolerance character education through social science learning in elementary schools and the level of student understanding in implementing tolerance character in everyday life in the school environment. The methods used were quantitative and qualitative. The data collection techniques used were interviews, observations, and questionnaires. The data sources were the principal, the fifth-grade teachers, and 46 students. Data analysis techniques used were percentage formula and interpreting the qualitative data. The results of this study indicated the implementation of tolerance character education through social studies learning in elementary schools was categorized as very good, and students' level of understanding in implementing the character of tolerance in everyday life at school was categorized as very good. Therefore, educational institutions must continue to pay attention to the character learning process even though it is only inserted into the core learning (field of study) so that the character education process can continue to run well and always socialize various learning models.